ANTI-CORRUPTION TOOLS IN THE SYSTEM OF DETINIZATION OF THE ECONOMY - YADUKHA, Sergey (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the study, attention is paid to the issue of the effectiveness of the state anti-corruption policy and the provision of systemic detinization of the national economy and economic relations in Ukraine. The purpose of the study is to substantiate the anti-corruption tools for ensuring the detinization of the national economy. It is shown that in the conditions of the intensification of the process of Ukraine's integration into the European community, ensuring a high-quality and effective state anti-corruption policy, systematic and complex de-criminalization of economic relations in Ukraine acquires a decisive and very important importance. The main factors of positive influence on the process of detinization of the economy of Ukraine have been determined, namely the adoption, improvement and implementation of appropriate regulatory and legal acts, liberalization of the legal field of entrepreneurial activity, reduction of the level of taxation of the income of individuals, improvement of the functioning of the financial system in terms of the targeted use of budget funds through the prohibition of budget funds offsets, restrictions on non-monetary payments, ensuring the stability of the national currency, positive changes in the structure of the money supply, improving the population employment system by creating new jobs. Measures to prevent manifestations of corruption and shadow economic activity in Ukraine are substantiated. Economic tools for combating corruption and the shadow economy of Ukraine have been developed. Organizational-economic and economic-legal methods of combating the criminal economy are defined, in particular, the maximum limitation of the use of cash in circulation in economic relations; control over the legitimacy of the way of life of individuals through the implementation of passporting and control over the movement of personal property, departure from the absolute application of the principle of presumption of innocence in the field of confirmation of the legitimacy of income received by individuals; amnesty of shadow incomes. Tools have been developed to increase motivation to limit shadow activities and increase the efficiency of entrepreneurship. It has been proven that in order to detinize the economy of Ukraine, it is necessary to create an optimal system of the operating economic mechanism based on the constructive cooperation of the branches of government. It was established that Ukraine should continue the practices of overcoming systemic corruption, which should become conceptual provisions: continuation of work on further improvement of anti-corruption legislation, bringing it into line with international standards; development of projects of regulatory legal acts on inclusion in acts of legislation, which determine the principles of activity and status of civil servants; development of virtuous behavior of persons authorized to perform state functions, etc.
Keywords: corruption; shadow economy; anti-corruption policy; detinization of the economy; state regulation; national economy